175k views
5 votes
Express x ^ - 2 + 27 ^ x in simplest form when x = 2/3

Express x ^ - 2 + 27 ^ x in simplest form when x = 2/3-example-1
User Hai Tien
by
5.0k points

1 Answer

4 votes

Answer:

33/4

Explanation:

x^-2 = 1/x^2

x^2 = ( 2/3 )^2

= 2^2 / 3^2

x^2 = 4/9

x^-2 = 9/4

27^x

27 = 3 x 3 x 3 = 3^3

27^x = 3^3x

= 3^( 3* 2/3 )

= 3*2

27^x = 6

x^-2 + 27^x

= 9/4 + 6

= 9/4 + 24/4

= ( 9 + 24 )/4

= 33/4

User Markus Wagner
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.